2015
DOI: 10.1161/jaha.115.002066
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double‐Blinded, Placebo‐Controlled Trial of Fibrinogen Concentrate Supplementation After Complex Cardiac Surgery

Abstract: BackgroundPostoperative bleeding after heart operations is still a common finding, leading to allogeneic blood products transfusion. Fibrinogen and coagulation factors deficiency are possible determinants of bleeding. The experimental hypothesis of this study is that a first-line fibrinogen supplementation avoids the need for fresh frozen plasma (FFP) and reduces the need for any kind of transfusions.Methods and ResultsThis was a single-center, prospective, randomized, placebo-controlled, double-blinded study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 27 publications
3
138
0
3
Order By: Relevance
“…shown that a fixed dose of 6g FC reduced post-operative bleeding and blood product transfusion (159). However, subsequent data analysis revealed that a reduced dose of FC would have likely yielded the same results (160).…”
Section: Fibrinogen Trials In Non-traumatic Haemorrhagementioning
confidence: 96%
“…shown that a fixed dose of 6g FC reduced post-operative bleeding and blood product transfusion (159). However, subsequent data analysis revealed that a reduced dose of FC would have likely yielded the same results (160).…”
Section: Fibrinogen Trials In Non-traumatic Haemorrhagementioning
confidence: 96%
“…In a study in 4202 cardiac surgery patients, Karkouti et al 163 observed a fibrinogen threshold of 2 g/dl below which blood loss increased. Several small RCTs have also shown that fibrinogen administration reduces bleeding in cardiac surgery 164,165 and a Cochrane review of cardiac and non-cardiac surgery trials reported a similar finding. 87 No previous study has evaluated the predictive accuracy of low fibrinogen levels.…”
Section: Laboratory Reference Testsmentioning
confidence: 80%
“…The amount of perioperative bleeding was defined in a heterogeneous way, either as a primary or (more frequently) secondary endpoint of the study. The following treatments have recently been evaluated for efficacy in reducing perioperative bleeding: use of transfusion algorithms based on point of care, 15 fibrinogen concentrate, 9,10,16,17 tranexamic acid/epsilonaminocaproic acid, [18][19][20] antithrombin-III, 21 heparin monitoring systems, 22 and shed blood processing. 23,24 Notably, the objective for all these treatments was a direct reduction in postoperative bleeding; however, in the majority of the cases, the primary endpoint was avoidance of transfusion.…”
Section: Perioperative Bleedingmentioning
confidence: 99%
“…Some might consider transfusion as a surrogate for perioperative bleeding, e.g., in studies exploring the effects of hemostatic drugs or techniques. 18,30 Nevertheless, even in this setting, some important methodological points must be considered. The most important consideration is that transfusions in cardiac surgery patients may be triggered by factors other than directly from bleeding-e.g., preoperative anemia and intraoperative hemodilution.…”
Section: Transfusions As Quality Of Care Measuresmentioning
confidence: 99%
See 1 more Smart Citation